Average Error: 0 → 0
Time: 4.5s
Precision: 64
\[\sqrt{x + 1} - \sqrt{x + 1}\]
\[\sqrt{x + 1} - \sqrt{x + 1}\]
\sqrt{x + 1} - \sqrt{x + 1}
\sqrt{x + 1} - \sqrt{x + 1}
double f(double x) {
        double r3372728 = x;
        double r3372729 = 1.0;
        double r3372730 = r3372728 + r3372729;
        double r3372731 = sqrt(r3372730);
        double r3372732 = r3372731 - r3372731;
        return r3372732;
}

double f(double x) {
        double r3372733 = x;
        double r3372734 = 1.0;
        double r3372735 = r3372733 + r3372734;
        double r3372736 = sqrt(r3372735);
        double r3372737 = r3372736 - r3372736;
        return r3372737;
}

Error

Bits error versus x

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0

    \[\sqrt{x + 1} - \sqrt{x + 1}\]
  2. Final simplification0

    \[\leadsto \sqrt{x + 1} - \sqrt{x + 1}\]

Reproduce

herbie shell --seed 1 
(FPCore (x)
  :name "sqrt(x+1) - sqrt(x+1)"
  :precision binary64
  (- (sqrt (+ x 1)) (sqrt (+ x 1))))